On some rhopalodinid sea cucumbers in the collections of the Natural History Museum, U.K. (Echinodermata: Holothuroidea: Dactylochirotida) - Thandar, Ahmed S.; Arumugam, Preyan (Zootaxa, 2011)
Several specimens of holothuroids in the collections of the Natural History Museum, U.K., identified as Rhopalodina lageniformis or simply Rhopalodina sp., were re-examined. Amongst these only the holotype of R. lageniformis is referable to this species. Of the four specimens misidentified as R. lageniformis, two are re-identified as R. parvalamina Cherbonnier and two described as a new species, R. cabrinovici. Another specimen, originating from Ghana, which is incorrectly identified as Rhopalodina sp., turned out to be a juvenile of Cucumaria congoana Heding and is subject of another paper describing additions to the holothuroid fauna of Ghana.